Reliability Distribution System on Load Break Switch Addition at PT. PLN (PERSERO) ULP Langsa City Using RIA-SECTION Technique Combined Method on ETAP 14.1.0 - Hasibuan, Arnawan; Bintoro, Andik; Salahuddin, Salahuddin; Meutia, Rizka Dwi (LPPM Universitas Andalas, 2022)
PT. PLN (Persero) ULP Langsa city is one part of UP 3 langsa, the LS-05 feeder in section two is the location for placing several office buildings. Continuity stable distribution of electrical energy is one of the most important aspects in the distribution system. Based on these problems, the writer was inspired to consuct research with the aim of testing the reliability of the feeders LS-05 and LL-4 which was installed with LBS manuver motorized at both ends of feeders. The LS-05 feeder with section method SAIFI value is 2.2739 times/ customers/ year and SAIDI Value is 8.41995 hours/ customers/ year. For LL-4 feeder witsh the same method SAIFI value is 2.28905 times/ customers/ year, then using RIA-Section technique combined method, LS-05 feeder have SAIFI value is 2,0219 times/ customers/ year, SAIDI value is 8,3082 hours/ customers/ year, LL-4 feeder have SAIFI value is 2.6574 times/ customers/ year and SAIDI 9.3008 hours/ customers/ year. This value indicates thet these two methods have succeeded in showing a reliability index is in accordance with SPLN due to the addition of LBS motorized.